Diabetes in India: Measuring the dynamics of a public health catastrophe - Patnaik, Pranav Kumar; Jain, Kamlesh K.; Chandra, P.; Pathak, Jaya; Raman, K. V.; Shah, Asha (Journal of Social Health and Diabetes, 2016)
Diabetes has emerged as a major concern in the Indian health-care setting but has been underrecognized as a significant challenge in the context of public health policy due to the necessity to handle acute health conditions. Trends obtained from national and regional surveys over time strongly point to the increasing diabetes burden. In addition, people with undiagnosed and prediabetes can aggravate the burden in the near future. Long-term concerns arise from the rapid transformations such as urbanization, rural–urban migration, and lifestyle changes happening across different populations of India. Attempts at creating a rational diabetes prevention and management policy are severely hindered by a lack of comprehensive, standardized data on diabetes prevalence, and trends in the evolution of the epidemic. The impact of diabetes is multifaceted, ranging from the clinical impact of higher secondary complications to personal, psychosocial, and financial effects on the individual which create a cycle of negative outcomes. Given the chronic nature of diabetes, the impact is likely to remain as a self-perpetuating burden on the health-care system. The magnitude, spread, and impact of the diabetes epidemic are substantial, and it has transitioned to being a pandemic with potentially catastrophic implications for the Indian Public Health System. It is therefore essential to create public health policy specific to diabetes care that is effective in reducing the multidimensional impact of diabetes catastrophe and prevent further multiplication of this pandemic.
Keywords: Diabetes mellitus; epidemic; prevalence; public health